2014
DOI: 10.1002/bip.22471
|View full text |Cite
|
Sign up to set email alerts
|

Structure of two crystal forms of sheep β‐lactoglobulin with EF‐loop in closed conformation

Abstract: Ovine β-lactoglobulin has been isolated from whey fraction of sheep milk and crystallized. The high-resolution structures of two crystal forms (triclinic and trigonal) obtained at pH 7.0 have been determined revealing that ovine protein, similarly to its bovine analog, is dimeric. Access to the binding site located in the eight-stranded antiparallel β-barrel in both structures is blocked by the EF loop that has been found in closed conformation. Similarly to bovine lactoglobulin (BLG), conformation of the EF l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(49 reference statements)
1
14
1
Order By: Relevance
“…Recently, Loch et al (2014) have published the structures of two crystal forms of ovine -Lg grown at high pH: a trigonal form that is identical to that reported by Rocha et al (1996) and a triclinic form (PDB entry 4nlj) that is distinct from both the bovine triclinic form (Brownlow et al, 1997) and that reported here. Interestingly, their high-pH forms both have the EF-loop in the closed position.…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…Recently, Loch et al (2014) have published the structures of two crystal forms of ovine -Lg grown at high pH: a trigonal form that is identical to that reported by Rocha et al (1996) and a triclinic form (PDB entry 4nlj) that is distinct from both the bovine triclinic form (Brownlow et al, 1997) and that reported here. Interestingly, their high-pH forms both have the EF-loop in the closed position.…”
Section: Figuresupporting
confidence: 85%
“…The space group was determined to be P1, with unit-cell parameters a = 37.40, b = 49.36, c = 49.42 Å , = 69.66, = 68.98, = 77.67 . The unit-cell parameters and the space group of the ovine -Lg crystals were distinct from those found previously for either the bovine protein (Brownlow et al, 1997) or the ovine protein (Rocha et al, 1996;Loch et al, 2014) and could not be transformed into a higher symmetry space group.…”
Section: X-ray Datacontrasting
confidence: 61%
See 2 more Smart Citations
“…Along with these findings, looking at the tertiary structure of the protein for the position of the amino acid residue in the chain provides important insight as to what gives rise to the separation. The Protein Data Bank has the β ‐lactoglobulin A, and β ‐lactoglobulin B, the tertiary structure of the proteins was observed. Position 64 is on a turn in on the outside and position 118 is on a beta strand inside the core of the protein.…”
Section: Discussionmentioning
confidence: 99%